Attenuation of 7-ketocholesterol-induced overproduction of reactive oxygen species, apoptosis, and autophagy by dimethyl fumarate on 158 N murine oligodendrocytes. Issue 169 (May 2017) - Zarrouk, Amira; Nury, Thomas; Karym, El-Mostafa; Vejux, Anne; Sghaier, Randa; Gondcaille, Catherine; Andreoletti, Pierre; Trompier, Doriane; Savary, Stéphane; Cherkaoui-Malki, Mustapha; Debbabi, Meryam; Fromont, Agnès; et al.
Graphical abstract: Highlights: 7-ketocholesterol induces oxiapoptophagy on 158 N murine oligodendrocytes. Dimethylfumarate (DMF) attenuates 7-ketocholesterol-induced apoptosis on 158 N cells. DMF attenuates 7-ketocholesterol-induced LC3-I activation into LC3-II on 158 N cells. DMF reduces 7-ketocholesterol-induced overproduction of O2 − and H2 O2 on 158 N cells. Abstract: Mitochondrial dysfunctions and oxidative stress are involved in several non demyelinating or demyelinating neurodegenerative diseases. Some of them, including multiple sclerosis (MS), are associated with lipid peroxidation processes leading to increased levels of 7-ketocholesterol (7KC). So, the eventual protective effect of dimethylfumarate (DMF), which is used for the treatment of MS, was evaluated on 7KC-treated oligodendrocytes, which are myelin synthesizing cells. To this end, murine oligodendrocytes 158 N were exposed to 7KC (25, 50 μM) for 24 h without or with DMF (1, 25, 50 μM). The biological activities of DMF associated or not with 7KC were evaluated by phase contrast microscopy, crystal violet and MTT tests. The impact on transmembrane mitochondrial potential (ΔYm), O2 − and H2 O2 production, apoptosis and autophagy was measured by microscopical and flow cytometric methods by staining with DiOC6 (3), dihydroethidine and dihydrorhodamine 123, Hoechst 33342, and by Western blotting with the use of specific antibodies raised against uncleaved and cleaved caspase-3 and PARP, and LC3-I/II. DMF attenuates the different effects of 7KC, namely: cell growth inhibition and/or loss of cell adhesion, decrease of ΔΨm, O2 − and H2 O2 overproduction, PARP and caspase-3 cleavage, nuclear condensation and fragmentation, and activation of LC3-I into LC3-II. The ability of DMF to attenuate 7KC-induced reactive oxygen species overproduction, apoptosis, and autophagy on oligodendrocytes reinforces the interest for this molecule for the treatment of MS or other demyelinating diseases.